Psychophysiological Stress Reactivity Relationships across the Menstrual Cycle. (16th December 2015) - Olson, Karen C.; Carroll, Haley A.; Lustyk, M. Kathleen B.
Abstract : While evidence suggests that women exhibit psychophysiological differences in stress reactivity across the menstrual cycle, the relationships among psychological and physiological stress reactivity states are not well understood. Healthy, normally cycling women (N = 44 ) participated in two counterbalanced laboratory sessions during the follicular and luteal phases where heart rate and subjective stress were assessed in response to stressors. There were no differences in the magnitudes of psychophysiological stress responses across the cycle. Psychological and physiological states were largely unrelated in the follicular phase but interrelationships were found in the luteal phase and these relationships were influenced by autonomic perception and trait anxiety. For women with high trait anxiety, autonomic perception appeared to buffer psychological and physiological stress reactivity during the luteal phase, suggesting that autonomic perception may be a protective factor for more anxious women during times of acute stress.